MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA SMAN 1 TANAH PUTIH KECAMATAN TANAH PUTIH - Norma Yulis; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this study originated from the observation while the researchers did the students of SMAN 1 Tanah Putih, researchers found differences in the motivation of siswa in physical education learning. Of these differences the researchers intend to seek to know what the real motivation of students through the study. Therefore, the purpose of this study was to determine how the student's motivation in physical education learning at SMAN 1 Tanah Putih. The research data was obtained from the distribution questionnaire filled by the sample. The sample in this study were students keals XI IPA 1 of 20 people (purposive sampling). Based on the research results can be concluded as follows: students' motivation to learn that the motivation of SMA Negeri 1 Tanah Putih Tanah Putih still have poor motivation. This means that to get a good learning outcomes one of its factors is motivation. The better aperson's motivation, the better the learning results obtained.Keywords : Motivation, Physical Education